Tribological behavior of polymer composites containing microcapsules and fibrous fillers: Finite element analysis and experimental verification. Issue 9 (11th January 2019) - Su, Chang; Wang, Huaiyuan; Li, Meiling; Ma, Yingjie; Zhu, Yanji
Abstract : In allusion to the repeatability and complexity of tribological experiments, numerical simulations were carried out successfully to study the effect of microcapsules (MCs) and carbon fibers (CFs) contents on the longitudinal frictional temperature and Von Mises stress transfers of composites. Novel MC‐(fibrous filler) finite element (FE) models for polyvinylidene fluoride (PVDF) composites were established by observing morphologies of truncation surface, thermogravimetric analyzer (TGA) test and mathematical calculation. The thermal‐stress coupled analysis revealed the influence of oily microcapsules (OMCs) and CFs on thermal conductivity, thermal expansion, and elastic modulus of composites had further transformed the tribological properties of polymer composites. Moreover, tribological tests were carried out scientifically to verify the high accuracy of the simulated results with the error <8%. Both the experiment and simulation results indicated that 20 wt% OMCs/8 wt% CFs/PVDF composites possessed the optimal tribological properties. These demonstrate the novel FE models can predict the tribological properties of polymer composites containing MCs and fibrous fillers legitimately. POLYM. COMPOS., 40:3453–3463, 2019. © 2019 Society of Plastics Engineers